2009
DOI: 10.1177/1082013208101022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Polyphenols Distribution and Antioxidant Activity during Fermentation of Some Underutilized Legumes

Abstract: The effect of fermentation on the polyphenol distribution and antioxidant activity of four underutilized legumes [Cajanus cajan L. Millsp (Pigeon pea), Vigna subterranea L. Verdc (Bambara groundnut), Sphenostylis stenocarpa Harms (African yam bean), and Phaseolus vulgaris L. (Kidney bean)] were investigated. The beans were cooked (12 h), soaked in boiled water (12 h), dehulled, and then cooked again (2 h). The cotyledons were drained, wrapped in jute sacks and left to ferment at 37°C (4 days) to produce condim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 28 publications
7
59
0
6
Order By: Relevance
“…An increase in hydroxybenzoic acid and (+)-catechin content was reported in spontaneously fermented lentils [69], while similar increase in free soluble phenols observed during the fermentation of some underutilized pulses [55]. Conversely, a reduction of conjugated forms of ferulic acid, p-cumaric, hydroxycinnamic derivatives, and bound phenols was observed during the fermentation of pulses [49,55]. Surprisingly, same authors reported the synthesis of tyrosol and an increase in free quercetin due to the hydrolysis of quercetin glucosides [49].…”
Section: Phenolic Compoundssupporting
confidence: 71%
See 3 more Smart Citations
“…An increase in hydroxybenzoic acid and (+)-catechin content was reported in spontaneously fermented lentils [69], while similar increase in free soluble phenols observed during the fermentation of some underutilized pulses [55]. Conversely, a reduction of conjugated forms of ferulic acid, p-cumaric, hydroxycinnamic derivatives, and bound phenols was observed during the fermentation of pulses [49,55]. Surprisingly, same authors reported the synthesis of tyrosol and an increase in free quercetin due to the hydrolysis of quercetin glucosides [49].…”
Section: Phenolic Compoundssupporting
confidence: 71%
“…These compounds impact pigmentation, lavor and taste in foods, and antioxidant activities and interact with proteins as a result of their radical-scavenging capacity [52]. Studies have shown that antioxidants contained in fermented pulses may mitigate the prevalence of some forms of cancer [53][54][55][56][57][58]. Ademiluyi et al [57] reported the hypoglycemic and antiacetylcholinesterase activities of fermented bambara in rats and atributed this to the presence of phenolic compounds and other phytochemicals.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…(40) Fermentation Previous researchers reported changes in composition of bambara groundnut during fermentation. (127)(128)(129)(130)(131) According to Fadahunsi and Sanni, (131) changes include an increase in crude protein, soluble solids, soluble protein in bambara groundnut tempe after 40 hour fermentation. The data obtained during tempe production showed an increase in the activities of the enzymes amylase, lipase, and proteinase as fermentation progressed.…”
Section: Milling and Roastingmentioning
confidence: 99%